2022
DOI: 10.1111/aje.12963
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of African savannah elephants (Loxodonta africana) on tall trees and their recovery within a small, fenced reserve in South Africa

Abstract: African savannah elephants (Loxodonta africana) can have detrimental impacts on trees; studies exploring elephant impact within small, fenced reserves, have lacked focus in determining elephant high‐use areas, the direct effect of fence line and tree recovery. The aim of this study is to assess whether elephants cause significant impact on trees in the small‐fenced Karongwe Private Game Reserve (KPGR) and to determine the levels of tree recovery. Trees ≥5 m in height were surveyed (n = 634 trees). Elephant loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 103 publications
0
13
0
Order By: Relevance
“…Areas of high human population and a decrease of suitable land were the best predictors of HEC in Mozambique [75], where it was found that areas with a human population density of <60 people/km 2 had lower HEC incidences than areas with higher human population densities. At low population densities, there is less interaction between humans and elephants, but also human driven destruction on elephant habitats and migratory routes might be lower [76]. Unfortunately, our time span for land cover change and GPS collar data did not cover exactly the same time span, during which conflict occurrences were assessed, making it difficult to relate changes in LULC to HEC incidences over time.…”
Section: Influence Of Elephant Home Ranges On Hecmentioning
confidence: 99%
“…Areas of high human population and a decrease of suitable land were the best predictors of HEC in Mozambique [75], where it was found that areas with a human population density of <60 people/km 2 had lower HEC incidences than areas with higher human population densities. At low population densities, there is less interaction between humans and elephants, but also human driven destruction on elephant habitats and migratory routes might be lower [76]. Unfortunately, our time span for land cover change and GPS collar data did not cover exactly the same time span, during which conflict occurrences were assessed, making it difficult to relate changes in LULC to HEC incidences over time.…”
Section: Influence Of Elephant Home Ranges On Hecmentioning
confidence: 99%
“…Ngene et al, 2009). Understanding how dominant vegetation types influence elephant movement patterns in response to spatiotemporal resource fluctuations offers an invaluable approach to their conservation in climate threatened and resource constrained arid areas (Gandiwa et al, 2013;Hema et al, 2017;IUCN, 2021;Ndaimani, 2018;Thompson et al, 2022).…”
Section: Résumémentioning
confidence: 99%
“…The African savannah elephant ( Loxodonta Africana ) respond to spatiotemporal variations in resource availability and quality over a wide variety of habitat landscapes as they require large food quantities to maximise foraging opportunities (Fryxell et al., 2004; Owen‐Smith & Chafota, 2012; Corpenicus, 2013; Van Moorter et al., 2013; (Carvalho & Campbell, 2023; Hema et al., 2017; Thompson et al., 2022). Several studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conducting relevant scientific research on wildlife conservation and communicating findings to decision-makers is an essential method to enhance conservation practices in line with environmental threats, such as habitat fragmentation and land-use change [1,2]. However, this alone is not sufficient to solve complex conservation issues such as human-wildlife conflict (HWC) [3].…”
Section: Introductionmentioning
confidence: 99%